2008
DOI: 10.1124/mol.107.044347
|View full text |Cite
|
Sign up to set email alerts
|

Abrogation of Hyperosmotic Impairment of Insulin Signaling by a Novel Class of 1,2-Dithiole-3-thiones through the Inhibition of S6K1 Activation

Abstract: A previous study from this laboratory showed that oltipraz and synthetic dithiolethiones prevent tumor necrosis factor-␣-induced hepatic insulin resistance via AMP-activated protein kinase-dependent p70S6 kinase (S6K) 1 inhibitory pathway. This study investigated whether oltipraz and a novel class of 1,2-dithiole-3-thiones were capable of preventing insulin resistance induced by hyperosmotic stress, thereby enhancing insulin-dependent signals, and, if so, whether the restoration of insulin signal was mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 46 publications
(63 reference statements)
0
16
1
Order By: Relevance
“…Insulin receptor substrate 1-mediated signaling is protected by 1,2-dithiole-3-thiones via S6K1 inhibition downstream of AMPK (Bae et al, 2007(Bae et al, , 2008. However, we found that rapamycin, an inhibitor of mTOR-S6K1 activity that induces the dissociation of mTOR-raptor complex by binding FKBP12, has no effect in apoptosis induced by AA ϩ iron (data not shown).…”
Section: Downloaded Fromcontrasting
confidence: 40%
See 2 more Smart Citations
“…Insulin receptor substrate 1-mediated signaling is protected by 1,2-dithiole-3-thiones via S6K1 inhibition downstream of AMPK (Bae et al, 2007(Bae et al, , 2008. However, we found that rapamycin, an inhibitor of mTOR-S6K1 activity that induces the dissociation of mTOR-raptor complex by binding FKBP12, has no effect in apoptosis induced by AA ϩ iron (data not shown).…”
Section: Downloaded Fromcontrasting
confidence: 40%
“…Oltipraz induces phase II enzymes in vitro and in vivo and increases glucose use against TNF␣ or sorbitol (Wang et al, 1999;Kang et al, 2003;Bae et al, 2007Bae et al, , 2008. In this study, the capacity of oltipraz to restore MMP in cells exposed to AA ϩ iron was examined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Paper II, we looked at an experimental technique known as Dominant Negative (DN) inhibition, which can result in only partial inhibition, and at how one has traditionally interpreted the results of such partial inhibitions [137,138]. Imagine three proteins: A, B, and C. We know protein A activates protein B, but are unsure if A activates protein C, or if it is another unknown protein that is responsible.…”
Section: Modeling Of Dominant Negative Inhibition Datamentioning
confidence: 99%
“…The number of diabetics worldwide is presently 347 million (2), with WHO projecting that diabetes will be become the 7th leading cause of death by 2030 (3), underscoring the need for novel therapies (4). Ribosomal protein (RP) S6 kinase 1 (S6K1), a downstream effector of the mTOR Complex 1 (mTORC1) signaling pathway (5), has emerged as a potential drug target in the treatment of T2DM (6)(7)(8). In earlier studies, we demonstrated that mice deficient for S6K1 are resistant to high-fat diet-induced (HFD-induced) obesity due to increased lipolysis (9) and a lesion in adipogenesis, which we subsequently traced to an impairment in the ability of stem cells to commit to the adipocytic lineage (10).…”
Section: Introductionmentioning
confidence: 99%